Fundamente - Geographie Oberstufe - Aunkofer, Marcus; Brodengeier, Egbert; Eger, Kathrin; Hoffmann, Thomas; Joachim, Jens; Lehnig, Bodo; Raschke, Nicole; Scholliers, Matthias (Ernst Klett Verlag, 2022)
Bindet laut Verlag konsequent die Agenda 2030 für nachhaltige Entwicklung ein.